ASEAN Regional Integration: The Philippines' domestic constraints to Physical connectivity - Tobit Abao; Hazel Jovita (Jurnal Studi Pemerintahan, 2022)
The ASEAN Master Plans for ASEAN Connectivity pursue the easement on the flow of goods, services, and people in the region as it endeavors to create a globally competitive single market and production base. However, data shows a substantial infrastructural gap among member-states with a significant constraint on physical connectivity at the regional level. This stark reality on the infrastructure gap is relevant to the Philippines as it continued to lag behind other ASEAN members on the infrastructure pillar of the World Economic Forum’s Global Competitiveness Index (WorldBank,2018).This paper looks into the domestic affairs of the Philippines in terms of financial capacity, governance scheme, and stability-security situation - and its implications on the country’s infrastructural gap in the ASEAN Region. Content analysis is used in exploring the literature, including ASEAN papers, academic essays, international organizations, government reports, and other related documents. Findings revealed that the Philippines exhibit wide infrastructural gaps that have long compromise edits competitiveness. Specifically, the Philippines faces severe domestic problems such as reduced spending on infrastructural development, coupled with critical institutional challenges and issues on stability and security. This paper argues the primacy of good governance as the precondition for a well-connected and sustainable infrastructure. Hence, reforms should focus on structuring domestic politics to address the infrastructural gaps. Changes may include the adaption of mechanisms to control corruption, ensures effective coordination among agencies, and improves the absorptive capacity in managing and implementing infrastructural projects.